Evaluasi Kesuburan Tanah pada Lahan Sawah Berbasis Sistem Informasi Geografis di Kecamatan Rendang - Dwiki Sinatrya Putra; Ida Bagus Putu Bhayunagiri; Ni Made Trigunasih (Fakultas Pertanian, Universitas Udayana, 2024)
Indonesia is an agricultural country which rice is the main food source The productivity of rice plants in Rendang District continues to decline. Rice productivity from 2011 to 2014 decreased from 6.51 tons/ha down to 5.28 tons/ha according to BPS data for Rendang District in 2021. This study aims to determine soil fertility status, limiting factors, and soil management efforts to improve soil fertility. This research was carried out in Rendang District from July to September 2023. The methods used include survey methods and soil tests in the laboratory. The chemical properties of the soil tested include CEC, base saturation, P-total, K-total, C-organic. Assessment of soil fertility status based on the results of soil chemical properties analysis is matched with Soil Fertility Status Assessment Criteria according to PPT in 1995. The results showed that there were two classes of soil fertility status, namely low and medium. Low fertility status is found in homogeneous land units I (Rendang, Nongan, and Pesaban Villages) and homogeneous land units III (Menanga Village). Low fertility status is being found in homogeneous land units II (Menanga, Rendang, Nongan, Pesaban Villages). The parameters that become limiting factors are P-total and K-total. Based on the results of the study, it is recommended to fertilize SP-36, KCl, and the addition of organic fertilizers according to the constraints of soil fertility parameters and an analysis of the fertilizer needs should be carried out to determine the right dose according to the cultivated plants.